From Caring Come Courage - Norhidayah, Mohamad (2018)
Kuantan, 17 March - Residential College Representatives 3 (PEKA 3) has successfully organized ‘From Caring Come Courage’ programme at the Seri Permai Welfare Home in Gambang, Kuantan Pahang. Nur Farisah as the program director explained on the programme's objective is to assist in the provision of daily activities for the benefit of the elderly while fostering mutual support in the needy society besides testing the resilience of students to accept new challenges.